2015
DOI: 10.1007/s11738-015-1820-0
|View full text |Cite
|
Sign up to set email alerts
|

Drought-induced changes in the actin cytoskeleton of barley (Hordeum vulgare L.) leaves

Abstract: Plants have developed different strategies to adapt to various stress conditions including drought. In the present study the drought-induced changes in the actin filament (AFs) network was studied, for the first time, in two barley cultivars of contrasting drought tolerance level. Detached leaves of drought-tolerant (cv. 'CAM/B1/ CI') and drought-susceptible (cv. 'Maresi') cultivars were dried under controlled conditions. The water relations as well as the transcript accumulation of actin (ACT11), actin depoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It has been suggested that actin filaments (AFs) may participate in drought tolerance, as they form a network connecting cell walls, plasma membranes and cellular compartments. Through this physical connections they may act as osmotic sensors, because a decrease of turgor changes the compression of AFs, what in turn may be recognized by the cell as a signal to switch on expression of drought-responsive genes (Huang et al, 2012 ; Sniegowska-Swierk et al, 2015 , 2016 ). Previous studies of AFs in CamB and Maresi genotypes showed that these genotypes differ in actin content and AF organization, both in optimal water conditions and after leaf desiccation (Sniegowska-Swierk et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that actin filaments (AFs) may participate in drought tolerance, as they form a network connecting cell walls, plasma membranes and cellular compartments. Through this physical connections they may act as osmotic sensors, because a decrease of turgor changes the compression of AFs, what in turn may be recognized by the cell as a signal to switch on expression of drought-responsive genes (Huang et al, 2012 ; Sniegowska-Swierk et al, 2015 , 2016 ). Previous studies of AFs in CamB and Maresi genotypes showed that these genotypes differ in actin content and AF organization, both in optimal water conditions and after leaf desiccation (Sniegowska-Swierk et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because cytokinesis requires new cytoskeleton and cell wall components, it is predictable that the cell wall and cytoskeleton-related proteins would change in response to drought. The cytoskeleton (i.e., microtubules and actin filaments) is a highly dynamic component, which is crucial for cell division, movement, morphogenesis, and signal transduction [168]. In proteomic studies, several cytoskeleton proteins, such as actin, kinesin motor protein, tubulin, profilin, actin depolymerizing factor, and fibrillin were decreased in response to drought stress (Figure 3B).…”
Section: Modulation Of Cell Structure and Cell Cyclementioning
confidence: 99%
“…In proteomic studies, several cytoskeleton proteins, such as actin, kinesin motor protein, tubulin, profilin, actin depolymerizing factor, and fibrillin were decreased in response to drought stress (Figure 3B). The actin genes were also reduced in drought-treated H. vulgare leaves [168]. The decrease of the cytoskeleton and cell cycle-related proteins implies that cell growth is suppressed during drought stress.…”
Section: Modulation Of Cell Structure and Cell Cyclementioning
confidence: 99%
“…Chitinase class II (Chi2) and actin isoform B showed 2-sided interaction in DT while both the proteins were not present in DS. Chitinase was detected in more abundance in response to environmental stress in majority crop plants, while actin responds as drought adaptation, by strengthening the cytoskeleton of the stressed tissue [77,78]. The high abundance of beta tubulin to WS suggests the stress-facilitated cytoskeleton remodeling via tubulin in DT.…”
Section: Unique and Newly Induced Proteins To Water Stress Enhancementioning
confidence: 99%